PENGEMBANGAN DESAIN MESIN PEMIPIL JAGUNG TENAGA MATAHARI - Firman Ardiansyah Ekoanindiyo; Antoni Yohanes; Endro Prihastono (Sekolah Tinggi Teknologi Industri Padang, 2022)
Agricultural land in Juwiring Village in the Cepiring sub-district, Kendal Regency, depends on rainwater for irrigating its rice fields. Rice fields in Juwiring village are planted with corn. In one year, farmers in Juwiring village can harvest corn 3 times. By using a solar powered corn sheller machine, farmers can save Rp. 20,000 per sack because there is no need to pay any more for the corn sheller, besides that with this machine you can save fuel because the fuel uses abundant solar power and the solar corn sheller machine is an environmentally friendly machine because it doesn't emit air pollution. In the previous study (Ekoanindiyo, 2020), from the results of the previous design there were several inputs from users, namely the hole for inserting corn was not too high so that farmers had to squat to put corn in. The diameter of the hole is not big enough so if there is corn with a large diameter then the corn cannot enter the hole. For the corn shelling process, it is inserted one by one into the hole so that the shelling process will take a long time. For the disposal site on the previous sheller machine there were two drain holes, namely the disposal of corncobs and the disposal of corn. When the machine is running, the corn cob does not come out of the cob drain hole but comes out together with the corn. The cobs and corn should come out separately, the corncob coming out of the corncob hole while the corn will come out of the corn dispensing hole. In the hole in the sheller machine place the sack so that the corn and corncobs can enter the sack. Development of a corn sheller machine design to improve the previous machine design including farmers in shelling corn do not need to squat so as to reduce fatigue when shelling. The holes for the cobs and corns to come out can be separated. The diameter hole for inserting corn is rather wide so that all sizes of corn can enter and when inserting corn into the machine you don't need one but you can do it directly in large quantities so that the shelling process can be completed more quickly. The research approach is with interviews and observations using anthropometric data of users. Using measurements of the body dimensions of farmers in the Village Farmer Group in Cepiring District as many as 5 people with elbow height body dimensions. The conclusion related to the development of the corn sheller machine design is the development of the corn sheller machine design using anthropometric data on the body dimensions of farmers in the Village Farmer Group in Cepiring District as many as 5 people. The body dimensions used are elbow height body dimensions. In this measurement the data used is the average or 50th percentile data or the average population so that users of moderate to tall stature can reach or use the machine